Zapożyczenia leksykalne w cyklolekcie - Wiertlewski, Stefan (Investigationes Linguisticae, 2019)
There is an abundance of loanwords (especially English) in Polish cycling sociolect. After a presentation of basic facts on the different types of borrowings (lexical loans, semantic loans and loan translations), about 600 English lexical loans divided into semantic classes (e.g. cycling disciplines, riders, equipment) are analyzed in the article. This is accompanied by a discussion of the most striking characteristics of their graphic, phonological, morphological and semantic adaptation into the Polish language.